Trajetórias: fissura labiopalatina e imagens - Victorio, Fernanda de Oliveira (Universidade Federal de São Carlos, 2022)
This dissertation contemplates anthropological reflections on the notion of person in the life trajectory of individuals with Complete Bilateral Transforamen Fissure (FTB), a specific type of cleft lip and palate and craniofacial anomaly, of variable presentation, that occurs during the development of the embryo. Attempting to think about the social relationships of patients at the Hospital for Rehabilitation of Craniofacial Anomalies (HRAC/Centrinho), associated with the University of São Paulo (USP), and located in the city of Bauru, this study focuses on the idea that the disease involves a set of latent phenomena that address individual and stigmatizing experiences. The research, which will be carried out from bibliographic studies and my experience as a carrier of the disease, will also rely on the power of images as a way to think about the construction of the notion of person of these individuals and express their human emotions through gestures memorials.

Cette thèse envisage des réflexions anthropologiques sur la notion de personne dans la trajectoire de vie des individus atteints de fente transforamen bilatérale complète (FTBC), un type spécifique de fente labiale et palatine et d'anomalie craniofaciale, de présentation variable, qui survient au cours du développement de l'embryon. Tentant de penser les relations sociales des patients de l'Hôpital de Réhabilitation des Anomalies Craniofaciales (HRAC/Centrinho), associé à l'Université de São Paulo (USP), et situé dans la ville de Bauru, cette étude se concentre sur l'idée que le la maladie implique un ensemble de phénomènes latents qui portent sur des expériences individuelles et stigmatisantes. La recherche, qui sera menée à partir d'études bibliographiques et de mon expérience de porteur de la maladie, s'appuiera également sur le pouvoir des images comme moyen de penser la constitution de la subjectivité de ces individus et d'exprimer leurs émotions humaines à travers des gestes mémoriels.
Trajectories: cleft lip and palate and images
Trajectoires : fentes labiales et palatines et images
Keywords: Estigma; Fissura labiopalatina; Hospital; Subjetividade; Stigma; Cleft lip and palate; Hospital; Subjectivity; Stigmate; Fente labiale et palatine; Hôpital; Subjectivité; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA; CIENCIAS HUMANAS::ANTROPOLOGIA::TEORIA ANTROPOLOGICA